Trapianto di rene da donatore anti HCV positivo: nostra esperienza - V. Sparacino; S. Calabrese; F. Caputo; V. Vinti; B. Oliva; A. Amato; V. Agnello; R. Mongiovì (AboutScience Srl, 2006)
Abstract non disponibile